Afferent sympathetic unmyelinated fibres with left ventricular endings in cats. - Casati, R (1979)
1. We recorded the electrical impulse activity of thirty-three single afferent fibres with left ventricular endings from the third and fourth left thoracic sympathetic rami communicantes of anaesthetized cats. Their conduction velocity ranged from 0.23 to 0.98 m/sec (group C). 2. The endings of each fibre were localized to the left ventricle by mechanical probing performed at the end of the experiment on the non-beating heart. No fibre had multiple sensory fields. 3. The impulse activity (0.95 +/- 0.2 impulses/sec) was spontaneous but most often a fixed temporal correlation between impulses and ventricular dynamics was not detectable. It was increased during occlusion of the thoracic aorta, I.V. administration of isoprenaline or infusion of saline. It was unaffected by asphyxia, haemorrhage and I.V. administration of acetylcholine. It was decreased during occlusion of inferior vena cava. Therefore these ventricular receptors appeared to be mainly sensitive to mechanical events. 4. The fibres were excited during the occlusion of the left main coronary artery, after a latency of 14.5 +/- 1.3 sec. They were also excited during ventricular fibrillation, exhibiting the highest values of impulse activity (2.51 +/- 0.4 impulses/sec). The increase in impulse activity during ventricular fibrillation was sometimes immediate and extreme, with peak frequencies of about 50 impulses/sec. 5. These spontaneously active ventricular receptors with unmyelinated nerve fibres participate in the transmission of the continuous impulse activity which from the cardiovascular system reaches the spinal cord through the sympathetic nerves and which is likely to contribute to the neural control of circulation. Thus the unmyelinated cardiac sympathetic afferents should not be considered as purely nociceptive in function.